Perayaan Melalui Makanan: Studi Komparatif Nasi Tumpeng dan Osechi Ryōri Jepang - Indah Puspita Sari (IZUMI, 2025)
People who live in a place celebrate certain days in the life cycle. Javanese people celebrate birthdays or harvest days by serving tumpeng rice. Japanese people have osechi ryiro food during the New Year celebration. The purpose of this research is to compare Javanese tumpeng rice and Japanese osechi ryiro. Both of these dishes are served during the celebration of a particular day and have meanings contained in each food. The methodology used is qualitative with data collection techniques reviewing books, journals, and articles that are in accordance with the theme. The theory used is Julian Haynes Steward's cultural ecology theory.  The result is that cone-shaped tumpeng rice has a meaning as a symbol of the majesty of God the Almighty Creator while the side dishes served have the meaning of the natural contents of the universe and each side dish has a meaning such as salted fish (mutual cooperation), catfish (hard work), and kale vegetables (flexibility). While osechi ryori is served in a box called juuboku that is layered with the meaning of accumulating pleasure for the rest of the year and other dishes such as ebi (longevity), buri (success) and konbumaki (joy). In conclusion, the Javanese tumpeng rice and the Japanese osechi ryiro are served on a specific festive day with the intention of serving a variety of dishes with meaning. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor